2019
DOI: 10.1002/adma.201805130
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Curvature Nanochannel‐Based Membrane with Anomalous Ionic Transport Behaviors and Reversible Rectification Switch

Abstract: Biological nanochannels control the movements of different ions through cell membranes depending on not only those channels' static inherent configurations, structures, inner surface's physicochemical properties but also their dynamic shape changes, which are required in various essential functions of life processes. Inspired by ion channels, many artificial nanochannel‐based membranes for nanofluidics and biosensing applications have been developed to regulate ionic transport behaviors by using the functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
101
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(103 citation statements)
references
References 82 publications
1
101
0
1
Order By: Relevance
“…[32,33] Previous studies have demonstrated that fluid and ion transport in CNT nanochannels is ultra-efficient, [32,34] which could potentially improve the performance of ionotronics. Also, the atomic inner diameter of CNTs is advantageous to mimic natural biological ion channels with similar pore sizes, [35] and the ultralong channel length of CNTs is beneficial for asymmetric modification of charges as well as integration of horizontally aligned chip-scale ionic circuits. Charge modification of CNT-based nanochannels can be readily conducted on the CNT terminals using well-established techniques.…”
Section: Introductionmentioning
confidence: 99%
“…[32,33] Previous studies have demonstrated that fluid and ion transport in CNT nanochannels is ultra-efficient, [32,34] which could potentially improve the performance of ionotronics. Also, the atomic inner diameter of CNTs is advantageous to mimic natural biological ion channels with similar pore sizes, [35] and the ultralong channel length of CNTs is beneficial for asymmetric modification of charges as well as integration of horizontally aligned chip-scale ionic circuits. Charge modification of CNT-based nanochannels can be readily conducted on the CNT terminals using well-established techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Such precisely prepared materials with nanoscale control on structure and functionalization would allow, for example, new perspectives in sensing. [ 1 ] Further strategies mimicking the functionality of biological channels include dynamic curvature nanochannel‐based membranes to regulate ionic transport [ 2 ] or flexible elastomer‐based microchannels for microfluidic devices. [ 3 ]…”
Section: Introductionmentioning
confidence: 99%
“…Through this curvature-based potential [Eq. ( 3 )] has been used in explaining many abnormal phenomena at micro/nano scales [ 38 , 39 ], the reliability of Eq. ( 3 ) in this case is validated by compared with the surface potential in MD simulation for parameters given above and displayed in Fig.…”
Section: Resultsmentioning
confidence: 99%